Design of ultra wideband phase shifter with improved scattering parameter performances - Dyg Norkhairunnisa, Abang Zaidel; Sharul Kamal, Abdul Rahim; Norhudah, Seman (IEEE, 2017)
Aiming to achieve Ultra Wideband (UWB) performance, this paper presents an improvement of the square-shaped phase shifter design, which covers from 2.8 GHz to 10.6 GHz by implementing step impedances in order to improve the impedance matching of the phase shifter, whilst leads to better scattering parameter results. The phase shifter design is formed by using multilayer technique where 3 layers of conductors are interleaved with 2 layers of substrates between each of the conductor's layer. This technique ensures the phase shifter design to be small in size. Computer Simulation Technology (CST) Microwave Studio is used in developing the design and optimization stage. Meanwhile the measurement is done by using Vector Network Analyzer (VNA). The square-shaped phase shifter with step impedances enhances the bandwidth up to 34% as compared to the conventional square-shaped phase shifter. Additionally, analysis on air gap and alignment is also presented in order to show how both conditions affect the performance of the proposed phase shifter design.